The Discursive Construction of Southeast Asia in 19th Century Colonial-Capitalist Discourse - Farish A. Noor (Farish Ahmad Noor), 1967- (Book collections on Project MUSE., 2016)
The nations of Southeast Asia today are rapidly integrating economically and politically, but that integration is also counterbalanced by forces ranging from hypernationalism to disputes over cultural ownership throughout the region. Those forces, Farish A. Noor argues in this book, have their roots in the region's failure to come to a critical understanding of how current national and cultural identities in the region came about. To remedy that, Noor offers a close account of the construction of Southeast Asia in the nineteenth century by the forces of capitalism and imperialism, and he shows how that construct remains a potent aspect of political, economic, and cultural disputes today.